Praktik Fraud Dalam Sistem Perbankan Ditinjau dari Peraturan Otoritas Jasa Keuangan - Rasyad, Pasha Athallah; Hadhani, Muhammad Gading Bintang; Tambunan, Daniel (Media Hukum Indonesia (MHI), 2024)
Fraud remains a serious problem in the financial sector, especially banking. Data from the Association of Certified Fraud Examiners (ACFE) in 2022 showed more than 2,000 fraud cases worldwide with losses of more than 3.6 billion USD, including 23 cases in Indonesia. In Indonesia, the Financial Services Authority (OJK), which was established in 2013, plays an important role in supervising this sector, implementing anti-fraud strategies to improve bank security. OJK guidelines in OJK Regulation (POJK) No. 39/POJK.03/2019 stipulate that every bank must develop an effective fraud control system and report fraud incidents that have a major impact within three working days. POJK also regulates administrative sanctions for banks that fail to carry out this reporting obligation, including fines and restrictions on business activities. This study uses a normative legal method to analyze the effectiveness of OJK's anti-fraud regulations and evaluate strategies that can be used to prevent and handle fraud. The results of the study show the importance of implementing an effective anti-fraud strategy, which includes prevention, detection, investigation, and monitoring to maintain the stability and health of the bank and protect the interests of customers.